The Development of Information System for Network Maintenance and Computer with Bootstrap Front-End Framework : Case study Navaminda Kasatriyadhiraj Royal Air Force Academy - ขุนทอง, นาถตยา (NKRAFA JOURNAL OF SCIENCE AND TECHNOLOGY, 2018)
The objective of this project is to develop an information system for network maintenance and computer of the Navaminda Kasatriyadhiraj Royal Air Force Academy. The study was analyze and design the system so that it is convenient to manage the maintenance and repair, data record and report. By using a computer to help manage such a system. Can access information efficiently and management information via the Internet. Administrator can browse the maintenance history quickly and easily. The application was developing by using MySQL as a database manager, using PHP as an application developing tool. Most of development was done using Microsoft Windows Server 2008 R2 and Bootstrap. The application divides the user into 3groups. The internal user group can and maintenance request and check the status of maintenance request through the website. The maintenance staff can handle computer and network maintenance job and can view maintenance history, maintenance statistics and report. And the administrator can manage user information and user permissions.